1964
DOI: 10.1002/cjce.5450420205
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer coefficients across ion‐exchange membranes

Abstract: A study of the interchange of hydrogen ion with various cations across polystyrene sulphonic acid ion‐exchange membranes has been made. The effects of membrane exchange capacity and crosslinking, solution concentration, temperature, counter ion valence and size on mass transfer rates were determined. The results indicated that ion and water transports across the membrane were dependent on the membrane water content, the ion concentration of the membrane, and the membrane ionic form. The mass transfer rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1965
1965
1975
1975

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Ultrasonic absorption studies by the Carstensen method were made on MnSQ4 in water and in 25 wt % dioxane in M2+OH2A2-5ZÍ;M2+A2- (89) On theoretical grounds step a is not expected to yield a separate relaxation peak. 546 It was suggested543 that the 200-Mc peak ought not to be assigned to step a but to step b.…”
Section: Solvation Numbers Foundmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonic absorption studies by the Carstensen method were made on MnSQ4 in water and in 25 wt % dioxane in M2+OH2A2-5ZÍ;M2+A2- (89) On theoretical grounds step a is not expected to yield a separate relaxation peak. 546 It was suggested543 that the 200-Mc peak ought not to be assigned to step a but to step b.…”
Section: Solvation Numbers Foundmentioning
confidence: 99%
“…Chem. Soc., 89,1765 (1967). methanol molecules in the solvation shell suggests a regular octahedral configuration in the first solvation shell under the conditions studied.…”
Section: K X-raymentioning
confidence: 99%
“…Data obtained by this method have been substantiated by independent measurements of membrane potentials [88]. It was also observed that there was no significant liquid film resistance in concentrated solutions [89]. It was also observed that there was no significant liquid film resistance in concentrated solutions [89].…”
Section: Current Density (Ma/cm 2 )mentioning
confidence: 69%
“…Ratios of chloride ion to hydrogen ion flux across these membranes (set no. [2][3][4] have been measured at 1.7 X for the o-naphthyl membrane and 1.8 X for the phenyl membrane at an external solution concentration of 0.1 mole/l. Values for the relative transport for the earlier propyl membranes of comparable water content vary between 1.5 X 10-3 to 4.5 x 10-3.…”
Section: Resultsmentioning
confidence: 99%